2011
DOI: 10.1093/anatox/35.3.188
|View full text |Cite
|
Sign up to set email alerts
|

Mephedrone (4-Methylmethcathinone)-Related Deaths

Abstract: Four deaths related to the drug 4-methylmethcathinone (mephedrone) are reported. Qualitative and quantitative analysis of mephedrone was performed by high-performance liquid chromatography-diode-array detection. Of the four deaths, one was attributed to the adverse effects of mephedrone, with cardiac fibrosis and atherosclerotic coronary artery disease as a contributing factor. A 49-year-old female insufflated mephedrone; analysis disclosed mephedrone in femoral venous blood (0.98 mg/L). The second death was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(91 citation statements)
references
References 12 publications
4
84
0
3
Order By: Relevance
“…These results are consistent with previous studies in animal models, reporting that, it induces substantial increases in blood pressure, heart rate, and cardiac contractility (Meng et al, 2012), in addition to acute cardiovascular toxicity characterized by hypertension and tachycardia (Sivagnanam et al, 2013;Nicholson et al, 2010;Regan et al, 2011;Maskell et al, 2011;Wood et al, 2010). Moreover, mephedrone consistently results in mydriasis, a specific and acute effect also observed after MDMA and amphetamine administration de la Torre et al, 2000de la Torre et al, , 2004Mas et al, 1999), although slighter in comparison with MDMA.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous studies in animal models, reporting that, it induces substantial increases in blood pressure, heart rate, and cardiac contractility (Meng et al, 2012), in addition to acute cardiovascular toxicity characterized by hypertension and tachycardia (Sivagnanam et al, 2013;Nicholson et al, 2010;Regan et al, 2011;Maskell et al, 2011;Wood et al, 2010). Moreover, mephedrone consistently results in mydriasis, a specific and acute effect also observed after MDMA and amphetamine administration de la Torre et al, 2000de la Torre et al, , 2004Mas et al, 1999), although slighter in comparison with MDMA.…”
Section: Discussionsupporting
confidence: 93%
“…There are two reported fatalities in the European Union in which mephedrone appears to be the sole cause of death and there are at least another 37 deaths in which mephedrone have been detected in post-mortem samples (Maskell et al 2011). Mephedrone was the first cathinone derivative to be 'risk-assessed' by the extended Scientific Committee of the EMCDDA (European Monitoring Centre for Drugs and Drug Addiction).…”
Section: Introductionmentioning
confidence: 99%
“…Urine drug screening in another series found that 16 of 17 specimens were positive for other drugs of abuse [13]. Postmortem toxicology testing has also revealed that concurrent use of other substances is common [32][33][34] Adverse Clinical Effects of Synthetic Cathinones Cardiac, psychiatric, and neurological signs and symptoms are the most common adverse effects reported in synthetic cathinone users who require medical care. There are four series detailing clinical effects of cathinones.…”
Section: Subjective User Effectsmentioning
confidence: 99%